A method for the analysis of 121 multi-class environmental chemicals in urine by high-performance liquid chromatography-tandem mass spectrometry - Zhu, Hongkai (J Chromatogr A, 2021)
Biomonitoring of human exposure to environmental chemicals has gained momentum in recent years. Biomonitoring methods often include analysis of a single class of chemicals with similar chemical properties. In this study, we describe a method that involves solid-phase extraction (SPE) coupled with liquid chromatography-tandem mass spectrometry (LC-MS/MS) and capable of measuring 121 environmental chemicals comprising plasticizers (PMs; n=45), environmental phenols (EPs; n=45), and pesticides (n=31) through a single extraction of urine. Urine samples were incubated with 20 μL of β-glucuronidase/arylsulfatase (4000 units/mL urine) (from Helix pomatia) buffered at pH 5.5 for 2 h at 37°C for optimal deconjugation conditions. We compared two extraction methods, namely liquid-liquid extraction and SPE, and the latter with ABS Elut NEXUS(®) cartridges was optimized to yield best extraction efficiencies. For increased resolution and chromatographic separation, two methods involving Ultra AQ C18(®) and Betasil(™) C18(®) columns were used. The MS/MS analyses were performed under both negative and positive ionization modes. The optimized method yielded excellent intra- and inter-day variabilities (relative standard deviation: 0.40–11%) and satisfactory recoveries (80–120%) for >95% of the analytes. The limits of detection were ≤ 0.1 for 101 analytes and between 0.1 and 1.0 ng/mL for 18 analytes. The optimized SPE LC-MS/MS method was validated through the analysis of standard reference materials and proficiency test urine samples and further applied in the analysis of 21 real urine samples to demonstrate simultaneous determination of 121 environmental chemicals in urine samples.